The Hero’s Journey of Kamado Tanjirou in Demon Slayer: Kimetsu no Yaiba - Savitri Khairunnisa Ikhtiari; Isti Siti Saleha Gandana (Passage, 2020)
Due to globalization, the popularity of manga and anime have increased remarkably. Manga refers to Japanese comic books, the series of which are often made into Japanese cartoons, usually called anime. Although several academic studies have used manga as data source for their research studies, it appears that not much has been done to examine the traits of the hero’s journey in manga. Hence, the aim of this study is to identify the stages of the hero’s journey in Demon Slayer: Kimetsu no Yaiba and to discover the inner transformation that the main character undergoes as a result of his journey. In order to accomplish this, two theories were adopted: the theory of hero’s journey proposed by Vogler (1992) and Weiland’s (2016) theory of character arc. The findings indicate that Demon Slayer: Kimetsu no Yaiba somewhat follows the stages of the hero’s journey described by Vogler’s (1992). Furthermore, the analysis of Tanjirou’s journey leads to a revelation of the inner transformation that he experiences, which is the positive change arc, and thus, making him as a willing hero.Keywords: Character arc, hero’s journey, manga, willing hero